Evaluation of Dog and Cat Patients with Intestinal Intussusception: A Retrospective Study in Egypt - Ibrahim, Nehal; Elmezyen, Abd-Elmegeed; Abd-Elmaboud, Mahmoud; Ismail, Ahmed Abdelbaset (Journal of Advanced Veterinary Research, 2022)
The purpose of this retrospective study was to clinically characterize intestinal intussusception in dogs and cats in Egypt. Medical records including signalment, clinical findings, diagnostic imaging features, treatment, and outcomes of dogs (n = 40) and cats (n = 30) with confirmed intestinal intussusception were reviewed. On presentation, ages were 2.56 Â± 1 years for dogs and 2.6 Â± 2.07 years for cats, the common breeds were German Shepherd (42.5%) and Persian cat (46.66%). Â Male dogs (67.5%) and tom cats (73.3%) were commonly presented. For diagnosis, the effectiveness of radiography was 67.5% for dogs and 70% for cats, whereas ultrasonography accuracy was 87.5% for dogs and 80% for cats. Three cases need further confirmation of diagnosis by computed tomography. Leukocytosis, thrombocytopenia, hyponatremia, hypochloremia, hypokalemia, and hypoalbuminemia were mostly observed in laboratory abnormalities. The most common site for intussusception noted in both dogs and cats was the ileocolic junction (ICJ; 50% and 47.7%, respectively). Based on intestinal health status, treatment methods included (MR) manual reduction (17.5% for dogs, 16.66% for cats) or manual reduction plus intestinal resection and anastomosis (IRA) (72.5% for dogs, 73.33% for cats). The overall survival rate post-operatively was 87.5 for dogs and 90% for cats. In conclusion, this study identifies clinical, laboratory, and diagnostic results, as well as treatment methods, applied for intestinal intussusception in dogs and cats in Egypt. Moreover, this study suggests that early presentation, diagnosis, and surgical intervention are necessary to improve the outcome and reduce the simultaneous complications.